Nanodrug Delivery Systems for Dermal and Transdermal Photosensitizer Drugs - Tedesco, Antonio C.; Primo, Fernando L. [UNESP]; de Siqueira Moura, Marigilson P. (Elsevier, 2017)
Skin is the largest organ in the human body and functions as a protective barrier. Molecules can penetrate the skin by three main routes: (1) intracellular (across the corneocytes), (2) intercellular lipids, and (3) appendages. Drugs are delivered to and through the skin for the treatment of skin diseases and systemic diseases, respectively. For dermatological applications, formulations are targeted to different layers of the skin to protect, enhance the appearance, or deliver medicaments to the skin. There is enormous interest in expanding the number of drugs delivered through the skin due to the perceived advantages of high patient compliance, controlled drug delivery, ease of termination of therapy, flexibility in the choice of drug administration site, and ease of altering the dose by controlling the application area and avoidance of first-pass effect. The recent appearance of nanotechnologies have opened up new opportunities for the development of nanosystems for topical and transdermal applications, and many other applications in the field of nanoscience. Many of those drug delivery systems have been specifically developed for skin applications of a huge amount of drugs, in medical and pharmaceutical applications. The goal of this chapter is to provide a comprehensive overview of the different types of DDS, their main characteristics and mechanisms of action in skin penetration, some applications already in use, and future prospects of nanosystems for dermal and transdermal drug delivery systems.
Keywords: Drug delivery systems; Nanocapsules; Nanoemulsion; Photodynamic therapy; Skin cancer; Skin permeation; Topical photosensitizers; Transdermal photosensitized nanomaterials